BS EN IEC 61076-8-103. Connectors for electrical and electronic equipment. Product requirements. Part 8-103. Power connectors. Detail specification for 2P+PE circular connectors with 20 A rated current and metal housing with push-pull locking and IP65/IP67 degree of protection (1st November 2019) - British Standards Institution,
No abstract available